2021
DOI: 10.1039/d0bm01172j
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing microenvironment by integrating negative pressure and exogenous electric fields via a flexible porous conductive dressing to accelerate wound healing

Abstract: Integrated directional exogenous electric field and negative pressure wound therapy via Ag nanowire polyurethane foam dressing to accelerate wound healing in pig model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The electrical stimulation devices commonly used in clinical treatment are mostly traditional electrical stimulation devices. Traditional electrical stimulation devices are mainly power devices that can generate different types of currents, such as DC power supplies (output DC), [ 38,48 ] signal generators (output AC and PC), [ 43,44,52 ] etc. Although they have achieved good results when applied to wounds, the traditional electrical stimulation devices are relatively large and difficult to carry around.…”
Section: Electrical Stimulation Treatment Devices and Methods For Skin Wound Healingmentioning
confidence: 99%
“…The electrical stimulation devices commonly used in clinical treatment are mostly traditional electrical stimulation devices. Traditional electrical stimulation devices are mainly power devices that can generate different types of currents, such as DC power supplies (output DC), [ 38,48 ] signal generators (output AC and PC), [ 43,44,52 ] etc. Although they have achieved good results when applied to wounds, the traditional electrical stimulation devices are relatively large and difficult to carry around.…”
Section: Electrical Stimulation Treatment Devices and Methods For Skin Wound Healingmentioning
confidence: 99%
“…Swelling is an essential property of cryogels, enabled the cryogels to absorb excessive exudate of the wound, and provide a moist environment bene cial to wound healing [40][41][42]. Also, the porous structure is conducive to cell migration and provides excellent oxygen permeability, which could accelerate wound healing [43,44]. Therefore, the swelling ratios of cryogels were evaluated, and the results are shown in Figure 2L.…”
Section: Resultsmentioning
confidence: 99%
“…3D conductive biomaterials demonstrate promising potential in electrodes for electrotherapy and scaffolds for skin tissue engineering. Chen et al reported an Ag nanowires-loaded foam demonstrating flexibility, enhanced conductivity, and long-term stability under physiological environment [ 226 ]. Due to the inherent antibacterial activity, good water-uptake capability, and electrical conductivity, the conductive foam could not only prevent infection and manage necrosis, but also implement annular oriented electrical field to wounds assisted by exogenous electrical fields.…”
Section: D Conductive Biomaterials For Wound Healingmentioning
confidence: 99%
“…First, they can be applied as compliant electrodes for electrotherapy. In general, the conductive wound dressings can facilitate ES to be well and uniformly conducted onto the wounds promoting the efficacy of electrotherapy [ 50 , 109 , 120 , 225 , 226 ]. Second, they can be used alone as wound dressings or tissue engineering scaffolds, demonstrating similar conductivity to human skin and supporting cellular activities, to accelerate wound healing performance.…”
Section: Summary and Perspectivesmentioning
confidence: 99%